2021
DOI: 10.25301/jpda.303.189
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Bonded Bracket Failure in Patients, Undergoing Fixed Orthodontic Treatment

Abstract: OBJECTIVE: The objective of our study is to determine frequency of bracket bond failure in relation to age, gender, most commonly involved tooth and quadrant. METHODOLOGY: In this descriptive cross-sectional study, a total of 100 patients with ages ranging from 10 to 30 years needing corrective orthodontic treatment were selected for the study. This survey was conducted at Altamash Institute of Dental Medicine, Karachi. The survey was initiated on 30th November 2019 and was concluded on 30th May 2020. A questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…In this study, younger patients demonstrated a statistically significant higher bracket failure rate than older patients, which is in agreement with Jung et al study [20]. In contrast, Khan et al and Sakrani et al studies showed no significant difference in bond failure with patients' age [8,21]. Of the bracket failures, 58.4% occurred in younger patients (≤20 years).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, younger patients demonstrated a statistically significant higher bracket failure rate than older patients, which is in agreement with Jung et al study [20]. In contrast, Khan et al and Sakrani et al studies showed no significant difference in bond failure with patients' age [8,21]. Of the bracket failures, 58.4% occurred in younger patients (≤20 years).…”
Section: Discussionsupporting
confidence: 91%
“…Debonding of brackets in this study was more commonly found in the mandibular dental arch (p < 0.01). Such results correspond to the previous studies carried out by other researchers [8,12,[21][22][23]. These higher failure rates were attributed to occlusal interferences because brackets on lower teeth can be affected by upper teeth cups during mastication, especially in case of increased overbite.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations